IS THE KWAP DEFINED BENEFIT PENSION FUND SUSTAINABLE IN THE LONG RUN? (International Journal of Banking and Finance, 2023)
The Retirement Fund Incorporated (KWAP) manages the civil servant pension fund. It is a statutory body governed by the Ministry of Finance to manage Malaysia’s civil employees’ pension scheme. In order to examine the fund’s long-term sustainability, this study simulates 560 scenarios to examine the required rate of return needed to fund this defined benefit pension based on four parameters, namely contribution rate, years of service, retirement age and life expectancy. Our results show: First, the minimum years of service for pension eligibility should be increased to 20 years. Second, a contribution rate of at least 13 percent per worker to KWAP is needed. Third, there are no significant changes in the required rate of return even though the retirement age is extended from 55 to 60. Fourth, this study shows that the contribution period is more crucial than the post-retirement period for the sustainability of the pension fund. As a policy suggestion, there is a need for the authority to set a minimum funding ratio for the KWAP pension fund to ensure its long-term sustainability.